2017
DOI: 10.4025/cienccuidsaude.v16i3.35539
|View full text |Cite
|
Sign up to set email alerts
|

<b> Usuários Com Estomia: A Vivência Do Autocuidado / Users With A Stoma: The Self-Care Experience <b>

Abstract: RESUMOO objetivo do estudo foi conhecer a vivência dos usuários na realização do autocuidado com a estomia. Pesquisa qualitativa, sendo realizadas oito entrevistas com usuários do Ambulatório de Estomias da Unidade Vila dos Comerciários, no município de Porto Alegre/RS. Os dados foram submetidos à análise de conteúdo, emergindo duas temáticas: "Influência da estomia no convívio social"; "Dependência e vínculo no autocuidado com a estomia". A estomia causa dependência para a troca do dispositivo coletor, delega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The stoma has a negative impact on the quality of life by changing the daily life activities, body image and interpersonal relationships of the individual. As a result of this effect, new social, economic, emotional, and physiological priorities may emerge for the individual 4 . As a result of studies, it has been reported that the daily activities of individuals with stoma are limited by approximately 3.46 times and that approximately 30-60% of individuals with stoma experience complications in and around the stoma after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The stoma has a negative impact on the quality of life by changing the daily life activities, body image and interpersonal relationships of the individual. As a result of this effect, new social, economic, emotional, and physiological priorities may emerge for the individual 4 . As a result of studies, it has been reported that the daily activities of individuals with stoma are limited by approximately 3.46 times and that approximately 30-60% of individuals with stoma experience complications in and around the stoma after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, social activities, such as work, school, sexuality, travel and interpersonal relationships, may be affected due to the fear of not being accepted and stigmatized by the social environment. 4,5 Nurses' education and counselling play an important role in helping individuals adapt to life with a stoma and maintain self-care.…”
Section: Introductionmentioning
confidence: 99%
“…The individual may feel emotions such as denial, guilt, anger, fear and hopelessness and may think of losing control by worrying about gas, odour and leakage from the stoma. In addition, social activities, such as work, school, sexuality, travel and interpersonal relationships, may be affected due to the fear of not being accepted and stigmatized by the social environment 4,5 …”
Section: Introductionmentioning
confidence: 99%